Empowerment for Increasing of White Oyster Mushroom Cultivation to the Next Level: Peningkatan Pemberdayaan Usaha Budidaya Jamur Tiram Putih Ke Next Level - Purwatiningsih, Rini (LPPM Universitas Yudharta Pasuruan, 2022)
This service partner is a white oyster mushroom cultivator and is classified as an economically productive partner, domiciled in Bedian Hamlet, Jambesari Village, Jambesari Darus Sholah District, Bondowoso Regency. He was domiciled in Bedian, Jambe Sari Village, Jambesari Darus Sholah District, Bondowoso Regency. Service Objectives: (1) partner to be more productive and have high entrepreneurial value (2) student can be improve the experience of studying outside the campus as one of the MBKM implementations. Implementation of activities includes: (1) Planning, (2) Administration preparation and Team coordination, (3) Continuous assistance from pre-production to post-production, (4) Evaluation (5) Controlling. The results of the activities: (1) Overcoming constraints on kumbung conditions, (2) Overcoming obstacles during the baglog filling process, (3) Overcoming obstacles in the baglog sterilization process, (4) Overcoming obstacles in the process white oyster mushroom production, (5) Overcoming obstacles in the post-production process, (6) providing added value to the production of white oyster mushrooms into mushroom chips.